Canine distemper infection in crab-eating fox (cerdocyon thous) from Argentina - Ferreyra, Hebe (2009)
Canine distemper virus (CDV) has been reported worldwide in wild carnivores and has been cited as the cause of population declines in some species. Crab-eating foxes (Cerdocyon thons) from El Palmar National Park, Argentina, were observed either dead or exhibiting clinical neurologic signs. Samples were taken from two individuals thatwere later found to bepositive for CDV by direct immunofluorescence in brain tissue. Based on molecular studies, the CDV strain had a high percentage of identity compared to CDV strains affecting dogs in Argentina. This is the first report of CDV infection in wild carnivores in Argentina.